2020
DOI: 10.1002/fam.2923
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of time‐averaged upward fire propagation speed of expanded polystyrene external thermal insulation composite systems masonery façade

Abstract: Summary Thermoplastic expanded polystyrene (EPS) external thermal insulation composite systems (ETICS) have caused serious results due to the ravages of frequent fire disasters in the world. Fire propagation of EPS ETICS was observed to be fast over exterior building wall, however, very few reports of time‐averaged fire propagation speed (FPS) is available currently. To have a quantitative understanding of FPS, a series of EPS ETICS façades were tested according to the intermediate‐scale Japanese JISA 1310 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In our previous work, a calculation method for FSR on the basis of test results from a series of tests is given [41]. When L EPS ≤ 0.3m,Q ≤ 1100 kW, and 17.3 ≤ FPI ≤ 31.3 (m/s 1/2 )/(kW/m) 2/3 , FSR in [cm/min] could be predicated by In this work, a new calculation method (current method) is proposed based on considering the HRR of window spilled flame and thermal parameters of EPS ETICS.…”
Section: Comparison Of Prediction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, a calculation method for FSR on the basis of test results from a series of tests is given [41]. When L EPS ≤ 0.3m,Q ≤ 1100 kW, and 17.3 ≤ FPI ≤ 31.3 (m/s 1/2 )/(kW/m) 2/3 , FSR in [cm/min] could be predicated by In this work, a new calculation method (current method) is proposed based on considering the HRR of window spilled flame and thermal parameters of EPS ETICS.…”
Section: Comparison Of Prediction Methodsmentioning
confidence: 99%
“…4(d) shows that the density has a negligible effect on the FSR. Thus, based on the analysis above and our previous work [41], we proposed a modified FPI (Φ) to evaluate the upward fire propagation potential of EPS ETICS as…”
Section: Correlation Of Instantaneous Fsr Versus Modified Fpi (φ)mentioning
confidence: 99%
“…As a result of the simulation, when CFRBFM is used as an indoor finishing material, the correlation between the ASET of temperature, visibility, and FED and the length of the floor area is shown in Equations ( 8)- (10), respectively. However, in Case 5, the ASET for FED was not measured during the simulation operation time and was excluded.…”
Section: Distribution Of Aset In Room Size Conditionsmentioning
confidence: 99%
“…In addition, heat spreading through building finishing materials contributes to the growth of fires, making it imperative to scrutinize the progression of indoor building fires regarding temperature elevation over time. This can be achieved by employing HRR (heat release rate) and THR (total heat release) values [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou [ 11 ] conducted an experimental study on average fire propagation speed (FPS) of the external wall using the expanded polystyrene thermal insulation system, finding that the relationship between the average FPS and the vertical distance is positively linear. Tao [ 12 ] studied the ignition behavior of different shapes of PMMA exposed to external heat radiation and found that cylindrical samples are easier to ignite than flat samples. The ignition time dropped with the decrease of the sample radius.…”
Section: Introductionmentioning
confidence: 99%